Effects of mineral stress on the vegetative development of greenhouse-grown bell pepper plants - Leonardo, Marcelo [UNESP]; Broetto, Fernando [UNESP]; Marchese, José Abramo; Bressan, Dayanne Fabrício [UNESP]; Marques, Douglas José [UNESP]; Coscolin, Renata Bruna dos Santos [UNESP] (My University, 2012)
The aim of this study was to evaluate the effects of mineral stress induced by fertigation on vegetative parameters of bell pepper (Capsicum annuum L.) grown in a protected environment. Subsequent applications of Ca(NO3)2 and KCl were adopted to change the electrical conductivity (EC) of the soil, which ranged from 1.5 (control) to 6.0 dS m-1. Organic matter was applied simultaneously to half of the plots to evaluate the possible attenuation of the effects produced by soil salinization. A signifi cant difference was observed in the number of totally expanded leaves and plant height between the different levels of soil EC. Application of organic matter to the soil was unable to attenuate the salinity effects of the treatments.
Keywords: Capsicum annuum L.; Fertigation; Salt stress; Salinization